2004
DOI: 10.1111/j.1523-1755.2004.66002.x
|View full text |Cite
|
Sign up to set email alerts
|

Retinoids in nephrology: Promises and pitfalls

Abstract: Retinoids not only are important in renal development, but also show promise as a new generation of renal medication and deserve to be tested in clinical trials to clarify their full potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
57
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 93 publications
2
57
1
Order By: Relevance
“…Although receptor-independent effects of retinoids have been described, most studies have shown that RAR and/or RXR play a role in retinoid-induced cellular effects through either genomic or nongenomic pathways (18,24,26). It was surprising that RAR␣, which is suppressed in HIV-infected cells, still played a critical role in atRA's effects on podocyte phenotype as supported by our data using the RAR␣ agonist and antagonist.…”
Section: Rar␣ Mediates the Effects Of Atra On Hiv-infected Podocytessupporting
confidence: 70%
See 2 more Smart Citations
“…Although receptor-independent effects of retinoids have been described, most studies have shown that RAR and/or RXR play a role in retinoid-induced cellular effects through either genomic or nongenomic pathways (18,24,26). It was surprising that RAR␣, which is suppressed in HIV-infected cells, still played a critical role in atRA's effects on podocyte phenotype as supported by our data using the RAR␣ agonist and antagonist.…”
Section: Rar␣ Mediates the Effects Of Atra On Hiv-infected Podocytessupporting
confidence: 70%
“…RAR are expressed in many tissues, including the kidney (18). They affect gene transcription either directly by binding to the RA-response elements of a pro-moter region (18,19) or indirectly by modulating transcription factors such as activator-protein 1 (20,21) or NF-B (22). Activation of cytosolic signaling molecules by retinoids also has been reported as an important pathway to induce leukemia cell differentiation (23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Their effect is mediated by either directly binding to retinoic acid response elements or indirectly, by regulating other transcription factors such as NK-jB or AP-1 (reviewed in (96)). Treatment with isotretinoin (13-cis RA) ameliorated rat antiThy 1.1 glomerulonephritis, with a reduction in TGFb gene expression (97).…”
Section: Disrupting Matrix Accumulationmentioning
confidence: 99%
“…After binding of ATRA to RAR, RAR forms homodimers or heterodimers with RXR, and the resultant complexes exert biological effects via binding to the retinoic acid response element (RARE) (37). Three putative RAREs are present in the regulatory region of the human nephrin gene (28).…”
mentioning
confidence: 99%